2007
DOI: 10.1080/10401230601163360
|View full text |Cite
|
Sign up to set email alerts
|

Relapse During Continuation Pharmacotherapy after Acute Response to ECT: A Comparison of Usual Care versus Protocolized Treatment

Abstract: The relapse rate associated with usual care following ECT was comparable to that of protocolized pharmacotherapy. This suggests that high relapse rates following ECT are not due solely to an "efficacy-effectiveness gap."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 11 publications
2
22
0
Order By: Relevance
“…We found that only 34% of all patients sustained remission, which is a striking result. This high relapse rate is one of the highest rates in literature, which vary between 44.7 and 64.3% in patients with mood disorders (17,18,21,23,28). Prudic et al (22) found disappointingly low remission rates with ECT in a community setting that are noteworthy to understand the real world, similar to our findings, but the follow-up duration was 6 months in their study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We found that only 34% of all patients sustained remission, which is a striking result. This high relapse rate is one of the highest rates in literature, which vary between 44.7 and 64.3% in patients with mood disorders (17,18,21,23,28). Prudic et al (22) found disappointingly low remission rates with ECT in a community setting that are noteworthy to understand the real world, similar to our findings, but the follow-up duration was 6 months in their study.…”
Section: Discussionsupporting
confidence: 77%
“…Early studies reported that 50% of patients who responded to ECT relapsed within the first 3 months without any continuation therapy (15,16). To date, only a few controlled continuation studies have been published with short follow-up durations, such as six months (17,18). The few studies in the literature with longer durations but having a small number of patients, an uncertain definition of remission, or with a retrospective design were not informative (19,20).…”
Section: Introductonmentioning
confidence: 99%
“…Nevertheless, previous reports, including the CORE study, indicate occurrence of post-ECT relapses within 2 to 4 months. 7,12,17 Unstratified randomization for presence of psychosis, melancholic features, medication resistance, and especially previous ECT courses in this study is a shortcoming that needs to be considered in future trials. It is difficult to draw a conclusion about whether the coadministration of sertraline or fortuitous inclusion of more patients who had previous ECT decreased the efficacy of ECT in the c-pharm early group.…”
Section: Limitationsmentioning
confidence: 88%
“…31 This is comparable to the recently reported 10% rate of ECT administration in US hospitals for recurrent depression. 12 Severity of depression in this study population was indicated by the 70.5% rate of medication resistance, the 65.2% rate of baseline suicidal thoughts and acts, and the mean baseline depression score of 64% of the maximum MADRS score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation